Entomological assessment of the risk of dengue outbreak in Abomey-Calavi Commune, Benin - PADONOU, GERMAIN GIL; Ossè, Razaki; Salako, Albert Sourou; Aikpon, Rock; SOVI, Arthur; Kpanou, Casimir; Sagbohan, Hermann; Akadiri, Yessoufou; Baba- Moussa, Lamine; Martin C. Akogbéto, Martin C. (My University, 2020)
Abstract Background: In May 2019, a confirmed dengue fever case was detected at the local hospital of Abomey-Calavi Commune in southern Benin. In Benin, there remains a dearth of literature concerning the distribution and biology of Aedes aegypti, the principal vector of dengue fever. This study was initiated by the Ministry of Health to partially fill this gap. The findings allowed us to assess the arboviral transmission risk incurred by the population of Abomey- Calavi to support programmatic decision-making. Methods: Entomological assessments were conducted in 5% of the houses, meaning 314 houses selected from 11 boroughs in Abomey-Calavi Centre district and 9 villages in Hêvié district. The surveyed breeding sites were water containers located in (domestic) and around (peri-domestic) the dwellings. When a container was positive (housing larvae), a portion of the immature population was sampled with a larval dipper and poured into labeled jars. Immatures were then reared to adulthood at the Centre de Recheche Entomologique de Cotonou (CREC) insectary. Adult mosquitoes were morphologically identified to species level by site and, a subsample of the collected Ae. aegypti mosquitoes were used for WHO susceptibility tube tests. Results: Of the 1372 adult Aedes specimens which emerged from the collected larvae and pupae, 1356 Ae. aegypti (98.83%), 10 Ae. luteocephalus, and 4 Ae. vittatus were identified. The Breteau indices were 160.2 in Abomey-Calavi Centre and 150 in Hêvié, whereas the House indices were 58.5% and 61.6% in the respective districts. WHO insecticide susceptibility tube tests showed that the mortality rates were 38.71% in Abomey-Calavi Centre and 85.71% in Hêvié for permethrin, and 72.22% in Abomey-Calavi Centre and 100% in Hêvié for deltamethrin. Conclusion: The two districts were highly infested by Ae. aegypti whose breeding sites were mostly man-made. Considering this, human behavioral change to substantially reduce the number of larval habitats is necessary to control the vector populations. As Aedes mosquitoes are day biters, the use of repellents such as ointments and smoke coils can also be useful.
Keywords: Transmission risk; Ae. aegypti; Arbovirus; Abomey-Calavi Commune